Aerodynamic and comfort characteristics of a double layer knitted fabric assembly for high speed winter sports - Konopov, I.; Oggiano, L.; Chinga-Carrasco, G.; Troynikov, O.; Saetran, L.; Alam, F. (Procedia Engineering, 2010)
In this paper, the double layer concept of knitted fabrics suitable for performance sportswear, where each layer is separate from the other, was studied. Aerodynamic properties of this assembly, where the base layer is made of 100% wool and an external layer made of 100% filament polyester were determined. Fabric samples were placed over a single diameter cylinder to imitate the human leg. The aerodynamic resistance was acquired at different speeds relevant to high speed winter sports. Evaluation of comfort properties (liquid moisture transport in multi-dimensions) of each layer as well as a double layer was performed and the liquid moisture management capacity of the assembly was classified. Results from the aerodynamic tests demonstrated that the base layer influences the aerodynamic characteristics of the entire assembly. Correlations between the geometrical parameters of double layer assembly and comfort and aerodynamic properties were established.